Pengaruh Gangguan Ritme Sirkadian Dengan Kejadian Diabetes Melitus Tipe 2 - Andityo Sumbarwoto; Isbandiyah Isbandiyah; Halida Nelasari; Geovani Rarung (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Globally, it is estimated that around 422 million adults had diabetes in 2014. Diabetics then have a higher risk of developing other diseases, such as: stroke and heart attack. Circadian rhythm disorders such as sleep disorders are one of the factors causing type 2 diabetes mellitus. This study isintended to increase knowledge and as a basis for further research on the effect of circadian misalignment in type 2 diabetes mellitus and to determine the effect of sleep disorders on type 2 diabetes. This research is a literature review with a database of articles on Google Scholar, PubMed, and Science Direct from 2016 to 2021 from national journals, and international journals indexed by Scopus and ISSN. Circadian misalignment discussed in this study is that sleep disorders affect the incidence of type 2diabetes mellitus. Lack of or little sleep will affect type 2 diabetes mellitus. This effect is mediated by a number of hormones such as melatonin, cortisol, leptin, and ghrelin. There is an effect of circadian misalignment on the incidence of type 2 diabetes mellitus.